Studi Literatur : Tafakkur dan Syukur dalam Kehidupan - Thoha, Muhammad Akbar; Hasibuan, Zainuddin Abdillah; Ardianti, Siti (ANWARUL, 2023)
This research is a literature study with descriptive qualitative research with library research that discusses two important concepts in human life, namely tafakkur and syukur. Tafakkur is the process of contemplating and thinking deeply to seek a deeper understanding of oneself, life, and creation. While syukur is an expression of gratitude and appreciation for all the blessings given by Allah SWT. In this literature study research, the author uses various written sources such as articles, journals and documents that are relevant to the study in this research. This study collects and analyzes a number of literatures that discuss tafakkur and gratitude sourced from the Al-Quran and Hadist. The results of the study show that tafakkur and syukur should be an important part of human daily life. By practicing tafakkur and syukur regularly, people can gain deeper wisdom and gratitude, as well as improve their relationship with Allah SWT and fellow humans. In conclusion, this literature review shows that tafakkur and syukur are important concepts in human life that can provide many benefits to human mental and spiritual health. Therefore, it is recommended that tafakkur and syukur be made an important part of people’s daily lives.